Mood disorders and circulating levels of inflammatory markers in a longitudinal population-based study. Issue 6 (20th September 2017) - Glaus, J.; von Känel, R.; Lasserre, A. M.; Strippoli, M.-P. F.; Vandeleur, C. L.; Castelao, E.; Gholam-Rezaee, M.; Marangoni, C.; Wagner, E.-Y. N.; Marques-Vidal, P.; Waeber, G.; Vollenweider, P.; et al.
Abstract : Background: There has been increasing evidence that chronic low-grade inflammation is associated with mood disorders. However, the findings have been inconsistent because of heterogeneity across studies and methodological limitations. Our aim is to prospectively evaluate the bi-directional associations between inflammatory markers including interleukin (IL)-6, tumor necrosis factor (TNF)- α and high sensitivity C-reactive protein (hsCRP) with mood disorders. Methods: The sample consisted of 3118 participants (53.7% women; mean age: 51.0, s.d. 8.8 years), randomly selected from the general population, who underwent comprehensive somatic and psychiatric evaluations at baseline and follow-up (mean follow-up duration = 5.5 years, s.d. 0.6). Current and remitted mood disorders including bipolar and major depressive disorders (MDD) and its subtypes (atypical, melancholic, combined atypical and melancholic, and unspecified) were based on semi-structured diagnostic interviews. Inflammatory biomarkers were analyzed in fasting blood samples. Associations were tested by multiple linear and logistic regression models. Results: Current combined MDD [ β = 0.29, 95% confidence interval (CI) 0.03–0.55] and current atypical MDD ( β = 0.32, 95% CI 0.10–0.55) at baseline were associated with increased levels of hsCRP at follow-up. There was little evidence for inflammation markers at baseline predicting mood disorders at follow-up. Conclusions: The prospective unidirectional association between current MDD subtype with atypical features and hsCRP levels at follow-up suggests that inflammation may be a consequence of this condition. The role of inflammation, particularly hsCRP that is critically involved in cardiovascular diseases, warrants further study. Future research that examines potential influences of medications on inflammatory processes is indicated.